2016
DOI: 10.1038/srep34845
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting of 3D Convoluted Renal Proximal Tubules on Perfusable Chips

Abstract: Three-dimensional models of kidney tissue that recapitulate human responses are needed for drug screening, disease modeling, and, ultimately, kidney organ engineering. Here, we report a bioprinting method for creating 3D human renal proximal tubules in vitro that are fully embedded within an extracellular matrix and housed in perfusable tissue chips, allowing them to be maintained for greater than two months. Their convoluted tubular architecture is circumscribed by proximal tubule epithelial cells and activel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
503
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 566 publications
(513 citation statements)
references
References 38 publications
10
503
0
Order By: Relevance
“…Analysis showed that this 3D kidney model exhibits cyclosporine toxicity and albumin uptake as they would in the human body ( Figure 6) [61]. This 3D model represents an improvement over 2D organ-on-chip models and a large step closer to developing a fully-functional kidney [61]. What once seemed like science fiction is now getting closer and closer to reality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis showed that this 3D kidney model exhibits cyclosporine toxicity and albumin uptake as they would in the human body ( Figure 6) [61]. This 3D model represents an improvement over 2D organ-on-chip models and a large step closer to developing a fully-functional kidney [61]. What once seemed like science fiction is now getting closer and closer to reality.…”
Section: Resultsmentioning
confidence: 99%
“…It was mentioned earlier how scientists plan to do this using fugitive inks [60]. A model for the kidney's proximal tubules has now been created using these techniques [61]. Researchers at Harvard's Wyss Institute.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xiaofeng Cui [27] and colleagues had applied a different strategy by using a natural osteochodral plug (extracted from bovine femoral condyles) as scaffold instead of synthesized polymers, then printed human chondrocytes mixed with modified PEG (polyethylene glycol dimethacrylate) onto the plug using thermal inkjet printer ( Figure 2C), and were able to generate integrated and stabilized new cartilage tissue after 6 weeks of culture. In another trial, Chang H. Lee and colleagues replaced the sheep native meniscus with a PCL-printed scaffold carrying connective tissue growth factor (CTGF) and transforming Smooth muscle cell [40] Epithelial cell [24] growth factor-β3 (TGF-β). These factors stimulated endogenous cells to reconstruct ECM (collagen) and enabled sheep to resume walking capacity about 12 weeks after surgery [14].…”
Section: Examples Of Bioprinted Tissues Bone and Cartilagementioning
confidence: 99%